Analyzing Hidden Fees in Digital Finance through the Lens of Sharia Economic Law - Suganda, Binti Istiqomah; Khoiruddin; Khulwah, Juhrotul (Al-Risalah, 2025)
The practice of hidden fees in digital financial transactions raises issues of fairness and transparency, potentially harming consumers and conflicting with the principles of Islamic economic law. This study aims to analyze the forms and mechanisms of hidden fees in digital financial services, assess their compliance with Sharia principles, and formulate fair cost-transparency strategies that are Sharia-compliant and free of elements of gharar. This research uses a normative legal research method with a qualitative approach through literature studies from secondary sources such as laws and regulations, fatwas from DSN-MUI, books, and related scientific journals. The results of the study show that hidden fees arise due to information asymmetry between service providers and users, weak standards of cost disclosure, and non-compliance with the principle of clarity in contracts (ijarah). This practice contains elements of gharar and tadlis, which render the contract legally defective under Sharia law. Theoretically, this study contributes to the development of contemporary Islamic contract law by demonstrating that the classical concept of ujrah ma'lumah (known compensation) must be reinterpreted in the digital context through mandatory real-time disclosure mechanisms. Practically, the findings reveal that transparency is not merely a regulatory compliance issue, but a fundamental requirement for the validity of ijarah contracts in digital transactions, thereby affecting the legal status of millions of fintech transactions in Indonesia. This study introduces the Sharia-Compliant Transparency Framework for Digital Finance as a novel integrated model combining maqāṣid al-syarī'ah approach, multi-stakeholder governance, and technology-based supervision (suptech) to strengthen Sharia compliance and consumer protection in digital transactions. Therefore, a comprehensive strategy is required in the form of strengthening regulations, implementing the principle of full disclosure, strict Sharia supervision, and enhancing Sharia-based digital financial literacy to ensure justice and transparency in digital financial transactions in Indonesia.